Urgensi Branding Produk dan Nomor Izin Berusaha (NIB) bagi Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Desa Rumpuk - Maysari, Nor; Hoirot , Nadiatul; Nasrullah, Nasrullah; Mufarihatul Afidah, Novi (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The Real Work Lecture program or Community Service Program is a mandatory program in the Tri Dharma of Higher Education which is carried out in Rumpuk Village with the aim of collaborating with the community and students with the aim of the welfare of the Rumpuk village community. The advice is all people who are involved in business or MSMEs. Typical production results from Rumpuk Village itself, namely in the form of woven mats from pandanus and the manufacture of furniture and furniture. Delivery for the marketing reach itself has reached the distance outside the district to outside the island. The marketing system is carried out through Word Of Marketing Mouth, wholesale orders to posting on social media. By conducting surveys and field observations, problem points were found which refer to the lack of a market for sales to the absence of legality for business actors. The implementation method carried out in this study is realized with the PAR or Participatory, Action, and Research method on how products can compete with good branding so that the realm of the legality of the business being undertaken is the process of making NIB certificates to residents and business groups to maximize business. through legality and strengthening product branding that can be used by the public to increase the value in the product and for the NIB certificate itself serves to complement personal administration in strengthening business in the future considering the growing era accompanied by increasingly sophisticated technology